(-5a)(-3a ²)
=
15a³
-5 x -3 = 15 ( negative times negative = positive)
a x a² = a³ ( when multiplying exponents, you add the exponents together )
Answer:
b=74
Step-by-step explanation:
You just gotta use sum of angles in a triangle and sum of angles on a straight line.
Answer:
No because (6, 4) is on the line
Step-by-step explanation:
x = 6
y = 4
1
4 >
------- 6 + 7
2
6
4>
------ + 7
2
4 > -3 + 7
4 > 4
that is not true so the answer is no because ( 6, 4) is on the line
Answer:
no.
Step-by-step explanation:
<em>b ∩ c </em>is the values that appear in both <em>b</em> and <em>c</em>.
<em>b ∪ c</em> is all the values in <em>b </em> and <em>c.</em>